2022
DOI: 10.1021/acscatal.1c04627
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of the Unusual Seven-Membered Methylenedioxy Bridge Formation Catalyzed by Fe(II)/α-KG-Dependent Oxygenase CTB9

Abstract: Methylenedioxy bridges (MDBs) are architecturally important motifs in natural products and bioactive molecules. Cercosporin, a typical perylenequinone pigment, contains an unusual seven-membered MDB, which has versatile biological and photocatalytic activities. Although cercosporin has been isolated, characterized, and studied for several decades, its biosynthetic pathway, especially the formation of the seven-membered MDB, has remained unclear. Here, we show that the formation of the seven-membered MDB is cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…A FAD-dependent monooxygenase, CTB7, has been proposed to catalyze the formation of the dioxepine ring of cercosporin (Chung and Liao, 2008); when the CTB7 gene was transferred into Cercospora zeina, it enabled cercosporin production (Swart et al, 2017), confirming the involvement of CTB7 in dioxepine ring formation. However, recent reports suggest that CTB9 and CTB10 also contribute to methylenedioxy bridge formation (de Jonge et al, 2018), which was confirmed by the crystal structures of CTB9 with various substrates and the subsequent sitedirected mutagenesis study (Liu et al, 2022). Practical approaches to activate or stimulate the perylenequinone pathways of natural PQ-producing fungi…”
Section: Confirmation Of Pq-linked Gene Functions By Heterologous Exp...mentioning
confidence: 78%
See 1 more Smart Citation
“…A FAD-dependent monooxygenase, CTB7, has been proposed to catalyze the formation of the dioxepine ring of cercosporin (Chung and Liao, 2008); when the CTB7 gene was transferred into Cercospora zeina, it enabled cercosporin production (Swart et al, 2017), confirming the involvement of CTB7 in dioxepine ring formation. However, recent reports suggest that CTB9 and CTB10 also contribute to methylenedioxy bridge formation (de Jonge et al, 2018), which was confirmed by the crystal structures of CTB9 with various substrates and the subsequent sitedirected mutagenesis study (Liu et al, 2022). Practical approaches to activate or stimulate the perylenequinone pathways of natural PQ-producing fungi…”
Section: Confirmation Of Pq-linked Gene Functions By Heterologous Exp...mentioning
confidence: 78%
“…Knockout of a PQ biosynthesis gene may decrease or eliminate the related enzymatic function ( Liu et al, 2022 ). Phenotypical and metabolic differences between wild-type strains and mutants can aid in the elucidation of gene functions, for example, the pentacyclic core structure of PQs confers a variety of colors ( Hu et al, 2019 ; Liu et al, 2022 ).…”
Section: Elucidating the Perylenequinone Biosynthetic Pathwaymentioning
confidence: 99%
“…78,79 CTB9 is another example of an enzyme that catalyzes the oxidation of 33 to generate the methylenedioxy bridge 34 in cerosporin biosynthesis (Scheme 5E). 80 2.1.3. C−N Bond Formation.…”
Section: Introductionmentioning
confidence: 99%
“…Isopenicillin N synthase (IPNS) catalyzes the production of isopenicillin N (IPN), the precursor of a β‐lactam ring contained natural products [7] . Recently, we reported that a Fe II /αKG‐dependent enzyme CTB9 catalyzes the seven‐membered methylenedioxy bridge formation during the biosynthesis of microbial phytotoxin cercosporin ( 1 ), [8] which is secreted by the widespread and destructive ascomycetous fungi genus Cercospora under sunlight [9]…”
Section: Introductionmentioning
confidence: 99%
“…[6] Isopenicillin N synthase (IPNS) catalyzes the production of isopenicillin N (IPN), the precursor of a β-lactam ring contained natural products. [7] Recently, we reported that a Fe II /αKG-dependent enzyme CTB9 catalyzes the seven-membered methylenedioxy bridge formation during the biosynthesis of microbial phytotoxin cercosporin (1), [8] which is secreted by the widespread and destructive ascomycetous fungi genus Cercospora under sunlight. [9] Anthraquinones and structurally related xanthones are widespread natural products in fungi and plants with distinctly potent biological activities, and many of them have long been used as medicines.…”
Section: Introductionmentioning
confidence: 99%